TUJUAN PENCIPTAAN MANUSIA DAN NILAI EDUKASINYA (KAJIAN TAFSIR TEMATIS) - Inong Satriadi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2009)
llah must have created universe, included mankind, with particular purposes. Among the purposes are to become His loyal servants, to represent Him as the caliph of the earth: to control and preserve nature and its entity, to be trusted by Him to manage the earth where other creatures were not able to assume such responsibility. The three purposes of creating mankind reflects high educational values. To worship is the main and the only reason for mankind to improve their faith to Allah. As a caliph of the earth, men are supposed to teach others to be come more professional in managing things and trusteeship teaches men to get closer and more responsible to Allah Kata kunci: al-ibadah, al-khalifah, al-amanah, taklif dan keimanan